Transcriptome sequencing and analysis of major genes involved in calcium signaling pathways in pear plants (Pyrus calleryana Decne.). (December 2015) - Xu, Yuanyuan; Li, Xiaogang; Lin, Jing; Wang, Zhonghua; Yang, Qingsong; Chang, Youhong
Abstract Background Pears (Pyrus spp. L.) are an important genus of trees that produce one of the world's oldest fruit crops. Salinity stress is a common limiting factor for plant productivity that significantly affects the flavor and nutritional quality of pear fruits. Much research has shown that calcium signaling pathways, mediated by Calcineurin B-like proteins (CBLs) and their interacting kinases (CIPKs), are closely associated with responses to stresses, including salt. However, little is known about the molecular mechanisms that govern the relationship between salt stress and calcium signaling pathways in pear plants. The available genomic information for pears has promoted much functional genomic analysis and molecular breeding of the genus. This provided an ample foundation for characterizing the transcriptome of pear under salt stress. Results A high-throughput Illumina RNA-seq technology was used to identify a total of 78, 695 unigenes that were successfully annotated by BLASTX analysis, using the publicly available protein database. Additionally, 2, 855 novel transcripts, 218, 167 SNPs, 23, 248 indels and 18, 322 alternative splicing events occurred. Assembled unique sequences were annotated and classified with Gene Ontology (GO), Clusters of Orthologous Group (COG) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis, which revealed that the main activated genes in pear are predominately involved in functions such as basic physiological processes, metabolic pathways, operation of cellular components, signal transduction mechanisms, and other molecular activities. Through targeted searches of the annotations, the majority of the genes involved in calcium signaling pathways were identified, among which, four genes were validated by molecular cloning, while 11 were validated by RT-qPCR expression profiles under salt stress treatment. Conclusions These results facilitate a better understanding of the molecular genetics and functional genomic mechanisms of salt stress in pear plants. Furthermore, they provide a valuable foundation for additional research on the molecular biology and functional genomics of pear and related species.